La fiesta de la virgen del Cisne en la ciudad de Loja como representación pictórica - Velez Elizalde, Mónica del Cisne (2016)
This research has the purpose of conducting to an analysis on the plastics aspects the representative identifying the popular party of Virgen del Cisne in the city of Loja within the historical, artistic and cultural context to understand as has been its development over time. This will allow to have firm theoretical foundations that will serve for the practical experimentation in which there have been recaptured the most relevant aspects of this celebration formed of the pictorial works, with what one tries to transmit from a personal vision the manifestations of the popular culture and to achieve an interaction with the spectators by means of the represented works.